2021
DOI: 10.3390/ijms221810014
|View full text |Cite
|
Sign up to set email alerts
|

NGF Eye Administration Recovers the TrkB and Glutamate/GABA Marker Deficit in the Adult Visual Cortex Following Optic Nerve Crush

Abstract: Eye-drop recombinant human nerve growth factor (ed-rhNGF) has proved to recover the retina and optic nerve damage in animal models, including the unilateral optic nerve crush (ONC), and to improve visual acuity in humans. These data, associated with evidence that ed-rhNGF stimulates the brain derived neurotrophic factor (BDNF) in retina and cortex, suggests that NGF might exert retino-fugal effects by affecting BDNF and its receptor TrkB. To address these questions, their expression and relationship with the G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…The main goal of the present study was to further investigate the role of VEGF/NGF interaction in the neuroretina by analyzing the effects of ed-NGF treatment in the STZ model of DR. As already showed by means of different models of retinal degenerations, ed-NGF are able to counteract RGC loss, and exerts protective and reparative actions through the normalization of neurotrophins and expression of TrkA receptors and its related intracellular pathways [ 21 , 23 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The main goal of the present study was to further investigate the role of VEGF/NGF interaction in the neuroretina by analyzing the effects of ed-NGF treatment in the STZ model of DR. As already showed by means of different models of retinal degenerations, ed-NGF are able to counteract RGC loss, and exerts protective and reparative actions through the normalization of neurotrophins and expression of TrkA receptors and its related intracellular pathways [ 21 , 23 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of eyes is that BDNF can be used locally to reduce its systemic side effects, but it needs to be given repeatedly, which will cause increasing risk of cataract, retinal ischemia, and endophthalmitis. (Rosso et al, 2021). These findings emphasized the role of NGF, especially BDNF, and provided a new perspective that eye administration might be a novel aspect in diseases involving both the brain and eyes, such as AD.…”
Section: Pros Pec T and Challeng Ementioning
confidence: 89%
“…More interestingly, Rosso, Pamela et al suggested that, in the context of retina and optic nerve damage, NGF intravitreal injection strongly enhanced the activity‐dependent TrkB expression in contralateral and ipsilateral visual cortex to improve visual acuity (Rosso et al, 2021). These findings emphasized the role of NGF, especially BDNF, and provided a new perspective that eye administration might be a novel aspect in diseases involving both the brain and eyes, such as AD.…”
Section: Prospect and Challengementioning
confidence: 99%
“…A different study indicated that the exogenous application of NGF promoted glutamatergic synapse activity via binding to Trk receptors. This promotion of glutamatergic synapse activity was regulated by potentiating the pre-synaptic release of glutamate ( 89 ). These data suggested that NGF released by glioma cells may enhance the glutamatergic NGSs and promote glioma growth.…”
Section: Retroaction Of Glioma Cells On Neuronsmentioning
confidence: 99%